The Healing Hermeneutics of Carnal Caring in Neonatal Intensive Care Units - Wepener, Cas (Nursing philosophy, 2026)
The importance of the incorporation of the body and the senses, especially touch, in caring for infants in neonatal intensive care units (NICUs) has been widely researched, resulting in practices such as skin-to skin care. This article takes a step back to scrutinise the underlying assumptions of these practices and links the notions of a bodily epistemology and relational ontology to the care of infants in the NICU by means of recent developments in the fields of philosophy and ritual studies. The temporal-spatial context of people involved in caring for hospitalised infants is explored through the lens of the concept of liminality, a concept that stems from the study of rites of passage and thus of people in a state of transition. The relatively new field of carnal hermeneutics is then engaged, first in a general sense with a special emphasis on bodies, flesh and skin as sources of knowledge, and secondly with an emphasis on bodies that are restricted in space, such as infants and their caregivers in NICUs. It is argued that a deeper understanding of the unique kind of liminality that is encountered by people such as mothers and infants in NICUs and of carnal caring emphasises the healing potential inherent in a family-centred care approach and highlights the need for implementation in NICUs. A better understanding of the "why" of carnal caring is essential for optimising the "how" of the praxis.